The development of a tool for GPs to manage overweight and obesity in children: A Delphi study - Maxime Adriana Maria van der Velden; Madelon van Tilborg-den Boeft; Sylvia Buis; Wilma Jansen; Patrick Jan Eugène Bindels; Marienke van Middelkoop (European Journal of General Practice)
Background General practitioners (GPs) could play an important role in the management of overweight and obesity in children. However, GPs experience different barriers and are in need of supportive tools. In order to support GPs to identify, address and refer these children, new tools should be developed.Objective To establish consensus among GPs about the content topics of a supportive tool to identify, address and refer children with overweight and obesity in general practice.Methods A two-round Delphi study was conducted with GPs identified as experts. A concept of a supportive tool was constructed based on focus-group interviews with GPs, practice nurses and parents of children with and without overweight and literature. The tool was categorised into five topics: identifying, initiating and continuing weight-related conversations, referring and evaluating a tool manual. GPs evaluated statements on the tool’s topics in terms of importance. All statements were rated on a 5-point Likert scale and consensus was set at ≥70% of respondents agreeing with the statements.Results GPs agreed that a supportive tool must contain a child’s specialised BMI calculator; examples to initiate and to continue weight-related conversations with parents and children; a map with available interventions; and a manual including information and resources about health risks of overweight and obesity during childhood.Conclusion The content topics of a supportive tool for GPs to identify, discuss and refer children with overweight and obesity were determined through a consensus-driven process. Further validation and assessment are required through a feasibility and implementation study.